Community Engagement at Tribal Land-Grant Institutions: A Tribal Approach to Reimagining the University-Community Relationship - Brian Kowalkowski; Lloyd Frieson, Jr; John L. Phillips (The University of Alabama, 2022)
University-community engagement is more critical than ever in order to address society's most pressing issues, such as climate change, health and economic disparities, and racial justice. In particular, public land-grant institutions and their faculty can harness their unique roles as teachers, researchers, and Extension educators who use science-based knowledge to meet the needs of communities. The founding principle of service to the common person is embedded in the land-grant mission, yet that tradition is being tested by external forces that are pushing land-grants toward greater selectivity in whom they serve and how they engage. Reimagining university-community engagement will require innovative thinking and new models of engagement. Tribal land-grant colleges and universities offer a unique approach to community engagement that may provide ways for universities to regain their footing as the "people's universities." This article will explore university-community engagement from a tribal perspective and provide an example of how one tribal land-grant college maintains strong connections with its community. A tribal model of community engagement may offer important lessons for public land-grant institutions and other organizations that seek to serve their communities in a more authentic way.